Kajian Penggunaan Lahan dan Alih Kegiatan Usaha - Andi Starina Fitri; Mukti Ali; Sri Aliah Ekawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2018)
Nusantara and Sulawesi roads are included in the traders' villages which have progressed so rapidly. This study aims to identify the physical characteristics of landuse types, determine the transfer of business activities and their impacts and develop strategies for land use development and transfer of business activities. This research includes qualitative and quantitative descriptive research. Data collection techniques in the form of observations, questionnaires, interviews, documentation, and inventory in related agencies. The data analysis techniques used are descriptive qualitative, quantitative, spatial analysis, building density, and SWOT. The results of this study are, based on the direction of the development of the Makassar City Spatial Plan characteristics of the types of activities on Nusantara and Sulawesi Roads that are designated as strategic trade and service centers in accordance with existing conditions. The transfer of business activities that took place was the function of the building, which at first the office converted into trade and services, education to the entertainment service industry, and residential buildings became shops. The main factor influencing the transfer of business activities is due to the existence of rules regarding the division of zones that are designated as centers of trade and services. Transfer of land functions have environmental, social, economic and cultural aspects. The direction of the strategy for the development of land use and the transfer of business activities is the regulation of spatial intensity for building density, control of high rise building buiding, provision of green paths and arrangement of trade buildings.